Desenvolvimento de grãos e produção de fitomassa do girassol em fun ção de aduba ções boratadas - Foloni, José Salvador Simoneti; Garcia, Rodrigo Arroyo [UNESP]; Cardoso, Celso Luiz [UNESP]; Teixeira, João Paulo; Filho, Hélio Grassi [UNESP] (My University, 2010)
Sunflower crop is a good option to no-tillage system; however, it is sensible to low B availability, what is common in tropical soils. The objective of this study was to evaluate the crop development, grain yield and grain size as affected by B fertilizer doses applied in the sowing and by leaf application. The experiment was conducted in controlled conditions, with four Borax doses (0; 1; 2 e 3 kg B ha-1) in the sowing interacting with four Boric Acid doses (0; 0,5; 1 e 2 kg B ha-1) by leaf application. The plants were managed until grain physiological maturity, when stems, leaves and capitula were sampled, besides the counting and weighing of two grain classes separated by size. The B fertilizer applied in the sowing lines increased total dry matter phytomass and grain yield. However, when interacting with high doses of B by leaf application, these values decreased. Grain size was increased with leaf fertilization, when B was not applied in the soil or with only 1 kg B ha-1 in the sowing line. On the other hand, when B was applied from 2 to 3 kg ha-1 in the crop sowing, high doses of leaf fertilizer affected grain filling.
Grain development and phytomass production of sunflower as affected by boron fertilization
Keywords: Boron; Helianthus annus L; Translocation